2021
DOI: 10.3201/eid2701.190782
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Fusariosis in Nonneutropenic Patients, Spain, 2000–2015

Abstract: Invasive fusariosis has a global increasing incidence and has emerged as a severe infection in nonneutropenic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 31 publications
1
15
2
Order By: Relevance
“…The main results are presented in Table 1. The majority of isolates were distributed within three SCs, namely, the Fusarium oxysporum SC (FOSC), the Fusarium fujikuroi SC (FFSC), and the Fusarium solani SC (FSSC), reflecting the epidemiology of human fusariosis (7,8). As expected, Fusarium spp.…”
mentioning
confidence: 55%
“…The main results are presented in Table 1. The majority of isolates were distributed within three SCs, namely, the Fusarium oxysporum SC (FOSC), the Fusarium fujikuroi SC (FFSC), and the Fusarium solani SC (FSSC), reflecting the epidemiology of human fusariosis (7,8). As expected, Fusarium spp.…”
mentioning
confidence: 55%
“…Among the 44 neutropenic patients, 41 (93.2%) had a hematologic condition compared to 5 of 14 (35.7%) among those who were non-neutropenic. In three of the latter five patients, the infection developed after allogeneic HCT given for a hematologic disease [28].…”
Section: Settingmentioning
confidence: 95%
“…As shown in Table 2, the incidence of invasive fusariosis in patients with hematologic diseases varies across different regions of the globe with the highest incidence reported in Brazil, compared with other countries such as Italy, USA, and Spain [1,12,[28][29][30][31][32][33][34][35].…”
Section: Incidence and Risk Factorsmentioning
confidence: 99%
“…Previous studies also showed a high mortality rate, which ranged from 60% to 80% at 90 days or 12 weeks. 5,6,25 The cause of relatively lower mortality rate in our study may be due to different characteristics of patients. There were fewer patients with haematologic malignancy (62%) than in other studies (80-92%), and more solid organ transplantation recipients (23%) in our study than in others.…”
Section: Ta B L Ementioning
confidence: 73%
“…There were fewer patients with haematologic malignancy (62%) than in other studies (80-92%), and more solid organ transplantation recipients (23%) in our study than in others. 5,25 This study has several limitations. First, this was a single-centre retrospective study with a small sample size.…”
Section: Ta B L Ementioning
confidence: 96%